2016
DOI: 10.7498/aps.65.074702
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of convective speeds of vortex structures in mixing layer

Abstract: Convective speed of a vortex structure in mixing layer is an important physical quantity for correcting aero-optics caused by the flowfield as a beam passes; however, knowledge about the dynamic characteristics of convective speed of a vortex structure in mixing layer is limited because the convective speed calculated from isentropic model, which is widely used at present, is a constant. Based on the large eddy simulation and ray tracing method, the optical path length (OPL) profile over the mixing layer flowf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For the shear layer (see A2), the Ma profiles along the vertical lines of x/H = 0.732, 1.588, and 2.505 are similar and they are all approximately symmetrical concerning the point of Ma = 3, which is the theoretical convection speed of the shear layer. [35] That is, the whole shear layer marked by two white dotted lines moves downstream at an average speed of Ma = 3. It is also observed that the shear layer spans the entire cavity length and this is consistent with the flow feature of an open cavity.…”
Section: Features Of the Flow Fieldmentioning
confidence: 99%
“…For the shear layer (see A2), the Ma profiles along the vertical lines of x/H = 0.732, 1.588, and 2.505 are similar and they are all approximately symmetrical concerning the point of Ma = 3, which is the theoretical convection speed of the shear layer. [35] That is, the whole shear layer marked by two white dotted lines moves downstream at an average speed of Ma = 3. It is also observed that the shear layer spans the entire cavity length and this is consistent with the flow feature of an open cavity.…”
Section: Features Of the Flow Fieldmentioning
confidence: 99%